2016
DOI: 10.1111/zygo.12258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Academic Degree and Discipline on Religious Beliefs and Evolution Acceptance: Survey at a Chilean University

Abstract: Affiliation with a scientific area or degree program could affect one´s religious beliefs and acceptance of evolution; however, this issue has been poorly studied. Moreover, little information is available regarding Chilean university scientists' views on religion and evolution. This study aims to provide the first documentation of the opinion of scientists at a Chilean University with regard to religion and evolution. This was done by conducting a personal survey of first and last year undergraduate students,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The relationship between religiosity and educational achievement across races creates potential for value clash. Marín and D’Elía (2016) found nonreligiosity was positively correlated with advanced educational attainment, though, for marginalized social groups (e.g., racial minorities), religiosity improves education outcomes (Lee, Puig, & Clark, 2007). Religious Blacks become more concentrated in the upper echelons of academia, even as ever greater proportions of their non-Black colleagues are nonreligious.…”
Section: Black Academics and The Culture Of The Criminology And Criminal Justice Academymentioning
confidence: 96%
“…The relationship between religiosity and educational achievement across races creates potential for value clash. Marín and D’Elía (2016) found nonreligiosity was positively correlated with advanced educational attainment, though, for marginalized social groups (e.g., racial minorities), religiosity improves education outcomes (Lee, Puig, & Clark, 2007). Religious Blacks become more concentrated in the upper echelons of academia, even as ever greater proportions of their non-Black colleagues are nonreligious.…”
Section: Black Academics and The Culture Of The Criminology And Criminal Justice Academymentioning
confidence: 96%
“…Science itself is often depicted as a conduit of secularism, and secularists demonstrate a high level of faith in science Witham 1997, 1998;Leuba 1916). To support this claim, researchers have pointed to the low percentage of scientists and those with a science education who express belief in God (Larson and Witham 1998;Martin and D'Elia 2016). However, this body of work does not assume that religion and science are in conflict (e.g., Martin and D'Elia 2016), but rather that religion is largely absent from science or that it plays a marginal role at best.…”
Section: Scientists' Definitions Of Religion and Spiritualitymentioning
confidence: 99%
“…To support this claim, researchers have pointed to the low percentage of scientists and those with a science education who express belief in God (Larson and Witham 1998;Martin and D'Elia 2016). However, this body of work does not assume that religion and science are in conflict (e.g., Martin and D'Elia 2016), but rather that religion is largely absent from science or that it plays a marginal role at best. Although recent sociological research has been critical of the conflict perspective (Baker 2012;Ecklund 2010;Norris and Inglehart 2004), it remains common among the general public and vocal new atheists critical of religion (i.e., Dawkins 2006).…”
Section: Scientists' Definitions Of Religion and Spiritualitymentioning
confidence: 99%
“…Marín and D'Elía (2016) presented a survey of 544 members of a southern liberal Chilean university, investigating whether their religious beliefs and acceptance of evolution were affected by the degree (first and last year bachelor degree students, graduate students, and faculty) and area (biology, chemistry, and physics) of academic formation. They found that nonreligiosity, as well as the acceptance of Darwinian evolution, increased with the possession of an advanced degree; this correlation was stronger for individuals who studied biology and physics than to those who studied chemistry (Marín and D'Elía 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marín and D'Elía (2016) presented a survey of 544 members of a southern liberal Chilean university, investigating whether their religious beliefs and acceptance of evolution were affected by the degree (first and last year bachelor degree students, graduate students, and faculty) and area (biology, chemistry, and physics) of academic formation. They found that nonreligiosity, as well as the acceptance of Darwinian evolution, increased with the possession of an advanced degree; this correlation was stronger for individuals who studied biology and physics than to those who studied chemistry (Marín and D'Elía 2016). The generality of the results presented by Marín and D'Elía (2016) can be strengthen by conducting two additional research steps: (1) resurveying with the same questions the then first year bachelor students at a time close to obtaining their degree––this exercise would allow to test if their beliefs changed over time; and (2) applying the same questions in another university with, among others, differences in socioeconomic, historical, and/or national backgrounds, as a way of testing the effect of these differences.…”
Section: Introductionmentioning
confidence: 99%